Harmonization of Local Wisdom of the Baduy Tribe Community as a Base for Strengthening Education Character in the Schools - Yogiarni, Tiara; Hikmatunnisa, Nenden Permas; Sri Wulan, Neneng; Fajrussalam, Hisny (Bulletin of Science Education, 2024)
Local Wisdom is a valuable unit of human achievement that reflects high historical, artistic and cultural values ??towards the identity of a society. This is a great capital for the formation of noble character. The strengthening local wisdom is considered important so that existing local wisdom does not simply erode. This research aims to analyze the local wisdom that exists in the Baduy tribe community, Kenekes Village, Banten as strengthening character education and exploring the key role of education in the socio-cultural realm in maintaining local wisdom. A qualitative approach was deemed suitable for use in this research. The result shows that Baduy tribe is a unique group of Indonesian people and has characteristics that are different from other tribes. The Baduy people are a society that is obedient and obedient in carrying out the mandate of their ancestors, their daily life is very strong with various applications of customary law which instructs them to always maintain and protect nature by not changing or destroying it. Instilling local wisdom inherently through education is a movement back to the basis of regional cultural values as part of efforts to build national identity and as a kind of filter in selecting other cultural influences. Keywords: Local Wisdom, Education Character, Community, Baduy Tribe